2 What's in a name? Defining and labelling disease and its role in reducing overdiagnosis and overtreatment. (4th December 2019) - McCaffery, Kirsten; Carter, Stacy; Thomas, Rae; Degeling, Chris; Nickel, Brooke; Copp, Tessa; Moynihan, Ray; Doust, Jenny; Glasziou, Paul; Barratt, Alex; Jansen, Jesse
Abstract : Changing disease or health risk definitions and labels where there is a case for no or little net benefit and significant harm, has the potential to affect millions of people worldwide. It appears, on the surface, to be a comparatively sustainable intervention to mitigate overdiagnosis and overtreatment, requiring only a one-off policy change. In practice however, changing disease definitions is an intensely complex, personal and political process requiring buy-in from clinical groups, patients and citizens. This symposium examines how changing disease/health risk definitions and labels might mitigate overdiagnosis and overtreatment. Taking a multidisciplinary perspective we consider how Psychology, Epidemiology, Deliberative engagement, Bioethics and History and Philosophy of science can contribute to our understanding of the impact of disease/risk definitions and labels on citizens, the health system and society in general. We identify possible solutions for this growing problem, including examining how this might be implemented by decision-makers responsible for defining conditions. We will have a series of brief 5 minute presentations followed by general discussion to collectively identify and further develop strategies to achieve change where it is warranted. Program of speakers (45 minutes): Introduction – Professor Kirsten McCaffery, University of Sydney. The Consumer's view – TBC The problem: The impacts of names on the named - a historical and philosophical perspective on disease definitions and labels – Dr Chris Degeling, University of Wollongong. Using Psychological methods to understand the impact of disease or disease risk labels and the effect of changing labels : Evidence from cancer labelling studies – Dr Brooke Nickel, University of Sydney Evidence from non-cancer labelling studies – Tessa Copp, University of Sydney Possible solutions: Engaging patients and public about the definition of conditions – Professor Stacy Carter, University of Wollongong. Re-labelling Gestational Diabetes: what do consumers want? A/Prof Rae Thomas, University of Bond. Defining the thresholds and boundaries for disease through expert committees . A proposed model for reform – Dr Ray Moynihan, Bond University. Changing practice in setting disease definitions through the Guidelines International Network – Professors Jenny Doust/Paul Glasziou, Bond University.